TOXICITY STUDIES OF A DEVELOPED HEPATOPROTECTIVE POLYHERBAL FORMULATION IN EXPERIMENTAL RATS - Sachdeva, Monika; Bajpai, Meenakshi; Razdan, B.K. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: In the present study acute, sub acute and sub chronic toxicity studies were performed on scientifically developed hepatoprotective polyherbal formulation (PF). PF consists of dried methanolic extracts of dried rhizome of Curcuma longa, dried leaves of Murraya koenigii, Nyctanthes arbortristis, and Occimum sanctum. Methods: In acute toxicity study, PF was administered once orally at doses ranging from 250mg/kg -5000 mg/kg. Body weight and food consumption was noted for a period of 14 days. Animals were also observed daily for any behavioral or other toxic changes. In sub acute toxicity study animals were administered drugs in dose range of 500-2000 mg/kg p.o. for 28 days. Sub chronic toxicity study was also performed. Drug in dose range of 250-1000 mg/kg was administered once daily for 90 days. At the end of the study blood was withdrawn for hematology and biochemical estimations. Animals were then sacrificed and liver, kidney, heart and brain were dissected out which were observed for any gross morphological changes. Weight of organs was also noted. Results: The results showed no evidence of any changes in body weight and food intake, hematological parameters, liver and kidney function test when compared with control. The organs did not show any evidence of gross morphological changes. Conclusion: It is concluded that PF, at a dose of 1000 mg/kg, is safe for long term treatment of hepatic disorders. Key Words: polyherbal formulation, hepatoprotective, acute, sub acute, sub chronic toxicity